Bagaimana Gaya Kognitif Siswa Mempengaruhi Proses Berpikir dalam Pemecahan Masalah Matematika - Anggriani, Emi; Suradi, Suradi; Danial, Danial (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
ABSTRACT This study aims to analyze how students’ cognitive styles influence their thinking processes in mathematical problem solving through a Literature Review approach using the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The review identifies and synthesizes various studies related to the relationship between cognitive styles—such as field-dependent (FD), field-independent (FI), reflective, and impulsive—and students’ critical thinking, creativity, collaboration, and communication skills in mathematics learning. The analysis results show that cognitive style has a significant influence on students’ thinking strategies, mathematical representations, and metacognitive abilities. Students with FI and reflective styles tend to think more analytically and systematically, while FD and impulsive students demonstrate strengths in cooperation and communication when provided with scaffolding support. Project-Based Learning (PjBL) and Problem-Based Learning (PBL) are found to be more effective when aligned with students’ individual cognitive styles. Furthermore, evaluation of logic-based educational programs and internal quality assurance systems is necessary to ensure adaptive and sustainable learning. Overall, understanding students’ cognitive styles is crucial for educators in designing flexible, reflective, and learner-centered teaching strategies to optimize higher-order thinking skills in the 21st-century education era, So it can be concluded that cognitive style can significantly influence students' thinking processes regarding thinking strategies and mathematical representation. Keywords: Cognitive Style, Mathematical Problem Solving, Critical Thinking, Creativity, Project-Based Learning